Language variation and change in academic writing : Recent trends through globalisation and digitalisation - Schmied, Josef; Bondi, Marina; Dontcheva-Navratilova, Olga; Pérez-Llantada, Carmen (Jan Kochanowski University Press, 2023)
This article discusses variation and change in academic writing, integrating different approaches, from English for academic purposes to lingua franca studies and from contrastive rhetoric to discourse analysis, and various comparative perspectives from national to genre/part genre (e.g. research article abstracts or conclusions) or careerspecific writings (e.g. BA, MA and PhD theses). It focuses on the interrelated development of discourse as social interaction in the context of technological affordances and societal demands and on the specific applications of the well-known trends of globalisation and digitalisation to non-native academic writing. Of course, the impact of recent changes varies with (sub-) disciplines, genres, and even individual researchers in their construction of careers and identities. The general trends, however, can be observed independently of whether we see them as functional necessity or advancement or threats to established conventions individually. A great number of small-scale empirical corpus studies should be able to provide a detailed mosaic where researchers can collaborate to provide a background for individual academic writers to choose from. Global rhetorical features (like IMRaD) and small-scale usages of pronouns are just examples of current variation and changes that are worth tracing in the wide field of metadiscourse that shapes academic interaction today, for the advancement of science communication and thus of science as a whole.